Penerapan Sosialisasi Perpajakan dan E-Filing Pada Kepatuhan Wajib Pajak Pelaku UMKM Di Kecamatan - Situmorang, Andrew; Manalu, Herold Moody (Universitas Pahlawan Tuanku Tambusai, 2024)
The target of this study is to observe how the implementation of e-filing and tax socialization has an impact on taxpayer compliance for MSME businesses in Parongpong District. Quantitative methods allow for precise measurement and greater generalization of data. Questionnaires were distributed to respondents and 50 MSMEs in Parongpong, West Bandung became the research sample. This research analyzes data using regression and descriptive analysis to determine the relationship between the variables studied. The results of this study show that actors responded well to the implementation of e-filing in the tax process (x = 3.944) as well as tax socialization (x = 3.684). In general, MSMEs are very obedient as taxpayers. The implementation of e-filing and tax socialization does not have a significant impact on taxpayer compliance for MSMEs in Parongpong, West Bandung, either partially or simultaneously. Keywords: e-filing, socialization, taxpayer compliance, msme